PENERAPAN PENGENDALIAN INTERN KAS DALAM MENUNJANG EFEKTIFITAS PENGELUARAN KAS PADA PT TOTAL BANGUN PERSADA Tbk (PROYEK KCME HEAD OFFICE PALARAN) - rina, Eny Yuliana (EKONOMIA, 2014)
Internal control system includes organizational structure, menthod and measures are coordinated to maintain the wealth of the organization, check the accuracy and realibility of accounting, should encourage efficiency and promote adherence to management discretion.